Development and Validation of a Job Resources Scale for Thai Nurses - Mahaveerachartkul, Korkiat; Sooraksa, Nanta (Journal of Community Development Research (Humanities and Social Sciences); Vol 11 No 4 (2561): October-November 2018DO - 10.14456/jcdr-hs.2018.26, 2018)
Job resources are work conditions that can help individuals achieve their career goals. The concept has a potential application in the nursing profession but a nursing job resources scale based on the Thai context does not yet exist. The purpose of this study was to develop and validate a scale that assessed the perceived levels of job resources of Thai nurses in the private sector. The study employed the exploratory sequential mixed-methods design (qualitative research followed by quantitative research) and was composed of two phases. First, the scale development began with individual interviews to explore what work conditions adequately represented the job resources of Thai nurses, followed by item generation and assessment, exploratory factor analysis, and reliability analysis. Second, the scale validation was achieved via confirmatory factor analysis, and convergent and concurrent validity analysis. The sample, consisting of 761 Thai nurses from 16 private hospitals in Bangkok, was randomly divided into three parts for different analyses, which resulted in the 15-item job resources scale (Cronbach’s alpha coefficient = .90), with three dimensions (CMIN/df = 1.50, CFI = .98, TLI = .97, RMSEA = .05, and SRMR = .04) that had the potential for use in studies in various disciplines related to nurse populations in Thailand. The indicators of the newly-developed job resources scale not only can enlighten educators concerning the crucial factors regarding the nursing job resources in the Thai context, but can also be used by practitioners as a guideline to increase professional accomplishments. Keywords: Job Resources, Scale Development and Validation, Thai Nurses